Necroptosis throws novel insights on patient classification and treatment strategies for hepatocellular carcinoma - Hu, Bowen; Gao, Jie; Shi, Jihua; Zhang, Feng; Shi, Chengcheng; Wen, Peihao; Wang, Zhihui; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Immunology, 2022)
Introduction: Necroptosis is a novel pattern of immunogenic cell death and has triggered emerging wave in anti-tumor therapy. Ever more evidence has suggested the potential associations between necroptosis and intra-tumoral heterogeneity. Currently, the underlying role of necroptosis remains elusive in hepatocellular carcinoma (HCC) at anti-tumor immunity and inter-tumoral heterogeneity. Methods: This study enrolled a total of 728 HCC patients and 139 immunotherapy patients from four transcriptome datasets and four immunotherapy datasets, respectively. The consensus clustering approach was employed to depict tumor heterogeneity of cancer necroptosis. Subsequently, our study further decoded the heterogeneous clinical outcomes, genomic landscape, biological behaviors, and immune characteristics in necroptosis subtypes. For each patient, providing curative clinical recommendations and developing potential therapeutic drugs were used to promote precise medicine. Results: Using WGCNA algorithm, necroptosis associated lncRNAs (NALR) were identified in HCC. Based on NALR expression, two heterogeneous subtypes were decoded with distinct clinical outcomes. Compared to C1, patients in C2 harbored superior pathological stage and presented more unfavorable overall survival and recurrence free survival. Then, the robustness and reproducibility of necroptosis subtypes were further validated via nearest template prediction (NTP) approach and classical immune phenotypes. Through comprehensive explorations, the C1 was characterized by enriched immune inflammatory and abundant immune infiltration while C2 possessed elevated proliferative and metabolic activities and highly genomic instability. Moreover, our results indicated C1 was more prone to obtain desirable benefits from immunotherapy. For patients in C2, numerous underlying therapeutic agents were developed, which might produce significant efficacy. Conclusion: This study identified two necroptosis subtypes with distinct characteristics, decoding the tumor heterogeneity. For individuated patient, our work tailored corresponding treatment strategies to improve clinical management.